Helping university students to ‘read’ scholarly journal articles: the benefits of a structured and collaborative approach - Fujimoto, Yuka; Hagel, Pauline; Turner, Paul; Kattiyapornpong, Uraiporn; Zutshi, Ambika (Journal of University Teaching and Learning Practice, 2011)
Academics often treat students’ discipline-specific literacy as unproblematic. In doing so they may underestimate the difficulties for university students as they move between subjects of study that may involve different disciplines, language genres and academic practices. This paper describes an initiative aimed at supporting students in reading academic articles in preparation for completing an essay for an assessment task. This initiative involved a structured and collaborative two-week tutorial exercise that provided students with practice in using a framework to extract the main ideas from academic readings. Students were surveyed after this exercise, and their reflections of its value are described in this paper. The findings of this study will inform further stages of the project which aim to develop and investigate practical ways to develop student’s academic literacy across several business disciplines.